Penggunaan Mahabbah Sebagai Proses Menuju Akad Perkawinan Perspektif Kaidah Al-Umuru Bi Maqashidiha - Mufti Kamal (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The purpose of this study is to understand the love magic as a process towards a contract in terms of fiqh al-umuru bi maqashidiha rules. The researcher used the approach method and the type of normative qualitative research with the type of library research. The results of the study indicate that the law of using the love magic as a process towards a marriage contract is very diverse depending on the purpose or intention and the conditions behind it, and on the other hand must use the criteria of the love magic which is allowed by scholars. When addressed to fellow Muslims, the law can become sunnah with certain criteria, haram with certain criteria, and becomes permissible or the law is returned to the law of origin of marriage. Meanwhile, when its use is aimed at non-Muslims, it also has various laws. If the target group is ahl al-kitab, then it can be a sunnah, for example to preach Islam, sometimes it becomes makruh, for example, the goal is good, positive or not playing with the person being addressed, but at that time or condition it is feared that there will be slander, and sometimes it will also become unlawful. If it is addressed to other than ahl al-kitab, the use of the the love magic is still allowed, it's just that he is not allowed to marry first before the non-Muslim who is intended for the use of the the love magic sympathizes with embracing Islam.